The Nyangahant ritual in the culture of Salako community at Kampung Pueh Lundu, Sarawak - Chelum, Alexander; Magiman, Mohamad Maulana; Tugau, Mangai; Mohd Saufi; Bokhari, Semsolbahri; Salleh, Norhuda (Turkish Online Jounal of Qualitative Inquiry, 2021)
This research is about the Nyangahant ritual in the culture of the Salako community in Kampung Pueh, Lundu, Sarawak. The Nyangahant ritual is the main ritual in the culture of the Salako community. To ensure that the rituals performed achieve the purpose and goal, the Nyangahant ritual must be performed according to the prescribed process. The situation is for the purpose of perfection to assure that the wish requested can be accepted by Jubata, the god of the Salako community. The main focus of this research is to identify the meaning of every ritual performed in the Nyangahant ritual in the Salako community. This study uses ethnographic methods for data collection using an ethnographic interview technique that involves the informants who are experts on Nyangahant ritual ceremonies, which are Tuha Adat, Nyangahant craftsmen, headman, and village chief. In addition, observation methods are also widely used in this research to deeply understand the ritual ceremonies of Nyangahant in the studied community. The observation techniques are conducted before, during, and after the Nyangahant ritual ceremony. This study found that the Nyangahant ritual ceremony is the ‘mother’ of all rituals for the Salako community. It became a priority in the executed ritual or other festivals. Moreover, the ritual also a prayer in the praying ceremony to ask for well-being and prosperity spared from all problems, calamities, and misfortune. Although the culture and customs of the Salako community have evolved mainly through the process of modernity in terms of heritage, they still held the ritual as a lifeline in their community.